Factors Affecting Underpricing Level during IPO in Indonesia Stock Exchange 2018 - 2019 - Deannes Isynuwardhana; Frizky Vega Febryan (Universitas Hayam Wuruk Perbanas, 2022)
The underpricing is an event that occurs when stock price in a primary market is smaller than that on secondary market. Indonesia has an increase of companies that experience underpricing every year, although there was a decline in 2019/ Yet, the decline was not significant. The purpose of the study was to determine the effect of factors such as company age, company size, and return on assets, financial leverage, earnings per share and current ratio on level of underpricing at the time of Initial Public Offering (IPO) on the Indonesia Stock Exchange for the period 2018-2018. This research was conducted on the companies that did an IPO on the IDX for the period 2018-2019 using method purposive sampling. There were 82 companies used and the method used was multiple linear regression analysis using SPSS software. The results showed that company size and earnings per share have a negative effect on the level of underpricing. However, the company age, return on assets, financial leverage and current ratio have no effect on the level of underpricing. This research expected to provide benefits to related parties, including for investors. Investors can consider the value of earnings per share and the size of the company when making investment. for issuers companies need to pay attention to value of Earning Per Share and the size of the company so it avoid underpricing and get expected profit for the company.